From cratonic interiors to deltaic shores: Tectonic and paleoclimatic influences on the diagenetic evolution of Khewra Sandstone, Salt Range, Pakistan - Muhammad Ajaz Abbasi; Imran Khan; Atif Iqbal Abbasi; Muhammad Jamil; Nawaz Ikram; Syed Ahsan Hussain Gardezi; Zulfiqar Haider Awan; Umair Aftab Choudary; Abdul Wali Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Editorial Expression of Concern: Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2026)

Environmental absorbed-dose quantities for natural radionuclides in soil using a simplified block phantom with an ICRP 110 comparison - Muhammad Ajaz; Haifa I. Alrebdi; Hannan Younis; K.S. Al-mugren (Journal of Environmental Radioactivity, 2026)

Retraction notice to ‘Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment’ [Environ. Pollut. 362, (2024) 125000] - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Performance enhancement of moisture diffusion energy harvesters by means of cobalt mixing and PVA coating of biochar - Hyeonoh Hwang; Ahmed Muhammad Ajaz; Xuanjun Jin; Azma Fakhar; Joon Weon Choi (Biomass and Bioenergy, 2026)

Structure-based virtual screening, molecular dynamics and MM-PBSA/GBSA analysis for the identification of novel CDK6 inhibitors against prostate cancer - Manzoor Ahmad; Muhammad Ajmal Khan; Ashraf Ullah Khan; Sadia Butt; Yahya Khan; Amir Zeb; Nadia Bibi; Aishma Khattak; Hina Ahsan; Ajaz Ahmad; Amin Ullah (In Silico Pharmacology, 2026)

Fabrication of moisture diffusion energy harvesters with oak mushroom logwood biochar for sensor operation, capacitor storage and structure performance relationships - Hyeonoh Hwang; Ahmed Muhammad Ajaz; Azma Fakhar; Joon Weon Choi (Biomass and Bioenergy, 2026)

Identifying the optimum irrigation strategies to maximize canola yield and profitability under climate change in Guanzhong Plain, China - Qaisar Saddique; De Li Liu; Ali Ajaz; Bin Wang; Xiaobo Gu; Muhammad Adnan; Puyu Feng; Yunfei Wang; Yufeng Zou; Huanjie Cai (Irrigation Science, 2025)
Climate change has a substantial impact on Chinese canola production, introducing a high level of uncertainty regarding future climatic conditions and their potential impact on canola production and gross margins. This study focused on identifying the optimal irrigation strategy to enhance the profitability of canola production in the Guanzhong Plain under future climate change conditions. In this study, we used the calibrated Agricultural Production Systems sIMulator (APSIM)-Canola model with the downscaled daily climate projections from 27 general circulation models (GCMs). These simulations were conducted under two Shared Socio-economic Pathways scenarios (SSP245 and SSP585) to assess the impact of climate change on canola phenology, rainfed and irrigated crop yield. We also conducted a gross margin analysis to assess the profitability dynamics of supplying irrigation to rainfed canola crop. An increase in rainfed canola yield was observed for all simulation periods, with an average increase of 11%, 15%, and 17% for the 2030s, 2060s, and 2090s, respectively. Supplementary irrigation using a threshold of 10–60% of plant available water capacity (PAWC) was found to be effective. Overall, it led to a 28% increase in yield for rainfed and an 85% improvement in gross margin. Beyond the threshold of 60% PAWC, additional irrigation did not result in statistically significant increases in yield and gross margin. We identified the optimal amount of irrigation for achieving maximum water productivity (WP) ranges from 85 to 150 millimeters. By avoiding irrigation when the soil’s plant available water capacity (PAWC) is over 60%, up to 44% of water can be saved. These findings could be useful for policymakers and farmers in planning for sustainable and enhanced canola production in the region.

Alleviation of vanadium toxicity through individual and combined supplementation of spermine and spermidine in soybean: Insights into oxidative stress management, detoxification mechanisms, and root exudates - Farwa Basit; Muhammad Khalid; Ali Bahadur; Javaid Akhter Bhat; Ajaz Ahmad; Parvaiz Ahmad (South African Journal of Botany, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Multivariate analysis of potential health hazards of manganese via dietary exposure of widely consumed vegetables amended with municipal solid waste - Asma Ashfaq; Zafar Iqbal Khan; Kafeel Ahmad; Hamid Raza; Muhammad Nazim; Ajaz Ahmad (Environmental Geochemistry and Health, 2025)

Integrated approach for wastewater remediation and biofertilizer development using Chlorella vulgaris in raceway ponds - Daniela Delgado Pineda; Mery Y. Flores Guetti; Ximena Rosado-Espinoza; Muhammad Ajaz Ahmed; Gilberto J. Colina Andrade; Ruly Terán Hilares (Algal Research, 2025)

Diffused sunlight assisted green synthesis of silver nanoparticles using Cotoneaster nummularia polar extract for antimicrobial and wound healing applications - Nasir Assad; Muhammad Naeem-ul-Hassan; Muhammad Ajaz Hussain; Azhar Abbas; Muhammad Sher; Gulzar Muhammad; Yasir Assad; Muhammad Farid-ul-Haq (Natural Product Research, 2025)

Retraction notice to “Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure” [J. Environ. Manag. 351 (2024) 119616] - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Unraveling the impact of high arsenic, fluoride and microbial population in community tubewell water around coal mines in a semiarid region: Insight from health hazards, and geographic information systems - Abdur Rashid; Muhammad Ayub; Xubo Gao; Yaoyang Xu; Zahid Ullah; Yong Guan Zhu; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Jörg Rinklebe; Sardar Khan; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

RETRACTED: Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Assessment of natural radioactivity levels in rice samples and their implications for radiological protection - Hannan Younis; Mian Mateen Ullah; Muhammad Adil Khan; Farooq Ahmad; Umair Azeem; Muhammad Waseem; Khurram Mehboob; Muhammad Ajaz; Wazir Muhammad (Isotopes in Environmental and Health Studies, 2024)

A comprehensive review of plant-based mucilages as promising candidates for water remediation - Sehar Javed; Zarfishan Zulfiqar; Zain Fatima; Gulzar Muhammad; Muhammad Ajaz Hussain; Muhammad Mushtaq; Muhammad Tahir Haseeb (Journal of Environmental Chemical Engineering, 2024)

Exposure to zinc oxide nanoparticles induced reproductive toxicities in male Sprague Dawley rats - Nagina Rehman; Farhat Jabeen; Muhammad Asad; Aneela Nijabat; Amir Ali; Safir Ullah Khan; Juan Pedro Luna-Arias; Zia-ur-Rehman Mashwani; Ayesha Siddiqa; Adhimoolam Karthikeyan; Ajaz Ahmad (Journal of Trace Elements in Medicine and Biology, 2024)

RETRACTED: Hydrogeochemical characteristics, stable isotopes, positive matrix factorization, source apportionment, and health risk of high fluoride groundwater in semiarid region - Abdur Rashid; Muhammad Ayub; Xubo Gao; Seema Anjum Khattak; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Sardar Khan; Jörg Rinklebe; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Aspects of superior photocatalytic dye degradation and adsorption efficiency of reduced graphene oxide multiwalled carbon nanotubes with modified ZnO-Al2O3 nanocomposites - Ajaz Ahmad Wani; Ryhan Abdullah Rather; Norazuwana Shaari; Umair Khan; Taseer Muhammad; Syed Modassir Hussain; Laila F. Seddek; Ahmed M. Abed (Journal of Environmental Chemical Engineering, 2024)

Samarium-based metal organic frameworks as high performance electrocatalyst for alkaline water splitting - Muhammad Mukhtar Sirati; Shagufta Sirati; Umay Amara; Ajaz Hussain; Dilshad Hussain; Muhammad Hanif; Khalid Mahmood; Hafiz Muhammad Asif; Muhammad Khalid; Muhammad Tariq; Farhan Siddique; Muhammad Yaqub; et al. (Fuel, 2024)

3D hierarchical microcubic morphological composite and its application for Bi-functional Humidity/Pressure sensing in TENG architecture - Shenawar Ali Khan; Muhammad Ajaz Ahmed; Mirza Mahmood Baig; Muhammad Muqeet Rehman; Yunsook Yang; Seung Goo Lee; Joon Weon Choi; Woo Young Kim (Chemical Engineering Journal, 2024)

RETRACTED: Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2023)

Geochemical control, water quality indexing, source distribution, and potential health risk of fluoride and arsenic in groundwater: Occurrence, sources apportionment, and positive matrix factorization model - Abdur Rashid; Muhammad Ayub; Jochen Bundschuh; Xubo Gao; Zahid Ullah; Liaqat Ali; Chengcheng Li; Ajaz Ahmad; Sardar Khan; Jörg Rinklebe; Parvaiz Ahmad (Journal of Hazardous Materials, 2023)

Environmental sustainable: Biogenic copper oxide nanoparticles as nano-pesticides for investigating bioactivities against phytopathogens - Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Irfan Ali Sabir; Ajaz Ahmad; Gadah Albasher; Afzal Ahmed Dar; Muhammad Ahsan Altaf; Awais Shakoor (Environmental Research, 2023)

Agricultural water management challenges in the Hunza River Basin: Is a solar water pump an alternative option?* - Madhav Prasad Dhakal; Amjad Ali; Muhammad Zafar Khan; Nisha Wagle; Ghulam Muhammad Shah; Muhammad Mudassar Maqsood; Ajaz Ali (Irrigation and Drainage, 2021)
In the glaciated mountains of the Upper Indus Basin of Pakistan, glacier‐ and snowmelt‐ based irrigation systems have been established over several centuries to secure water for cultivation. However, these systems are now facing several challenges, being sensitive to climate change and thus exposed to the resulting extreme events such as glacial lake outburst floods (GLOFs) and flash floods, also difficult terrain and access paths, male outmigration, limited technical capacity and a weak policy and governance system. Hence, exploring the potential options for overcoming the challenges and irrigating arable barren land could lead to economic prosperity and environmental gains. A literature review, stakeholder consultation and semi‐structured questionnaire survey in two villages of the Hunza River basin was conducted to synthesize information in different domains. Information on the irrigation system and its sources, water distribution/allocation system, challenges and adaptation strategies were collected, and based on community preferences, an alternative irrigation technological package was established to overcome the challenges and irrigate barren land. A customized solar water lifting pump with an efficient micro‐irrigation package was piloted which proved to be climate resilient. The system is simple to adopt, uses clean energy for operation and is economically feasible, with a benefit–cost ratio of 4.96 and a payback period of around 11 years.

Analyzing adaptation strategies for maize production under future climate change in Guanzhong Plain, China - Qaisar Saddique; Huanjie Cai; Jiatun Xu; Ali Ajaz; Jianqiang He; Qiang Yu; Yunfei Wang; Hui Chen; Muhammad Imran Khan; De Li Liu; Liang He (Mitigation and Adaptation Strategies for Global Change, 2020)

Effect of biochar and phosphate solubilizing bacteria on growth and phosphorus uptake by maize in an Aridisol - Muhammad Arif Ali; Muhammad Mustansar Ajaz; Muhammad Rizwan; Muhammad Farooq Qayyum; Muhammad Arshad; Sajjad Hussain; Niaz Ahmad; Muhammad Amjad Qureshi (Arabian Journal of Geosciences, 2020)

STATISTICAL DATA COLLECTION METHODOLOGIES OF IRRIGATED AREAS AND THEIR LIMITATIONS: A REVIEW - Ali Ajaz; Poolad Karimi; Xueliang Cai; Charlotte De Fraiture; Muhammad Saleem Akhter (Irrigation and Drainage, 2019)
Inconsistencies in the statistical data sets of irrigated areas at the national level could have considerable implications for policies developed for food and water security. Remote sensing can address this issue; however, doubts about its reliability inhibit its protagonist role. Methods that integrate both remote sensing based and statistical data sets seem expedient, and they are more likely to be acknowledged by policymakers. Therefore, it is important for scientists to know the basis and limitations of statistical data sets which originate at the country level. Data collection methodologies of irrigated areas have been reviewed for seven Asian countries, namely China, India, Pakistan, Bangladesh, Nepal, Indonesia and Thailand. Factors causing the uncertainties in data, and the limitations of data collection methodologies, were highlighted. Also, an irrigation density distribution analysis was conducted to understand the relation of spatial spread pattern of irrigated areas and uncertainty in their statistical records. It was found that irrigated area statistics are mostly based on information originating from water user associations and farmers, which is either self‐reported or collected through interviews during surveys and censuses. The main causes of discrepancy were lack of resources to frequently enumerate the irrigated land, inconsistency in data collection methodologies, unaccounted secondary crops, illegal and unregulated water use, and bureaucratic and political constraints. Irrigation density distribution analysis showed that largely scattered irrigated areas might be prone to a lack of comprehensive and frequent enumeration. Furthermore, dense irrigation regions might have potentially unrecorded irrigated areas where temporary or supplementary irrigation arrangements are made by marginal farmers. © 2019 John Wiley & Sons, Ltd.

New insight in staphylococcin research: bacteriocin and/or bacteriocin-like inhibitory substance(s) produced by S. aureus AB188 - Sadia Saeed; Sheikh Ajaz Rasool; Samia Ahmed; Tanweer Khanum; Muhammad Bashir Khan; Atiya Abbasi; Syed Abid Ali (World Journal of Microbiology and Biotechnology, 2006)